Talking about teams within a team building context: a discourse analytic study - Chapman-Blair, Sharon (Rhodes University, Faculty of Humanities, Department of Psychology, 2001)
This research initiative responds to some of the issues raised by theoretical challenges leveled at Industrial Psychology (postmodernism), and practical challenges in the workplace (the use of teams) by investigating notions of what a team is via the postmodern methodology of discourse analysis. The research explores "team talk" "“ repertoires of speech employed by individuals to construct particular versions of "the team" for specific effects, of importance given emphasis placed on shared understanding, expectations and goals in a "team" . A Rhodes University Industrial Psychology Honours class required to work as a team (having participated in a team building exercise), as well as their lecturers who facilitated the team building process were interviewed to obtain "talk" to analyse. This uncovered a multiplicity of meaning, namely four ways of speaking about (constructing) the team. These repertoires are explored in terms of how they are constructed, how they differ across context and speakers, how they interrelate and what they function to achieve. The educational team repertoire constructs academic hierarchy, justifies individualism, positions members as experts and maintains distance from interpersonal processes. The machine repertoire divides work and interpersonal issues, regulates productivity and constructs team roles (defining individual activity and "team fit" ), but is inflexible to change. The family repertoire voices emotive aspects to maintain cohesion via conformity, leaderlessness, group identity and shared achievement, but cannot accommodate conflict or workpersonal boundaries. The psychologised team repertoire constructs the team primarily as a therapeutic entity legitimately creating individual identities (and expertise) and facilitating personal growth, but this flounders when support in the "team" fails. Given that each repertoire has a different emphasis (reflective learning versus work processes versus building relationships versus personal growth), there are slippages / clashes between repertoires. This postmodern look at "the team" thus assists in recognizing and problematising these multiple meanings and identifying practical implications.
Keywords: Discourse analysis; Teams in the workplace